Analysis of Tires Product Quality at PT. Berkah Andal Sukses, Medan - Halim, Varine Agustine (ADPEBI, 2022)
This research was conducted to know that improving the quality of a product is very important for the company so that customers continue to have consistency in buying these products and the level of customer satisfaction will also increase because one of the things that consumers pay most attention to is the quality of the product to be purchased. The research method used in this research is the descriptive qualitative method. The data collection methods used are unstructured interviews and observation methods. From the results of an unstructured interview with one of the customers with the initials